1996
DOI: 10.1183/09031936.96.09010072
|View full text |Cite
|
Sign up to set email alerts
|

Respiratory infections and the autumn increase in asthma morbidity

Abstract: Unexplained autumn increases in hospital admissions for asthma have been reported in many countries, including the United States, Canada, England and Wales.To investigate the role of infection, the association was tested between hospital admissions for asthma and respiratory infections among preschool children in Metropolitan Toronto, Canada during the period 1981 to 1989. The seasonal pattern in overall hospital utilization was assessed by admissions for nonrespiratory diseases. Time series analysis was used … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
52
2
6

Year Published

1998
1998
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 98 publications
(67 citation statements)
references
References 29 publications
7
52
2
6
Order By: Relevance
“…Our study indicates an increase in daily ED visits for Ͻ18-year-old Albertans for ILI, shortness of breath, and cough/congestion that was significantly higher (RR, 1.24; 95% CIs, 1.11, 1.40) in 2014 than during the same period of time in 2013. Previous studies have identified increases in asthma admissions in Canada and other countries during the period of July to October (7,8). Seasonal upswings in ERV activity, while other respiratory viral pathogens are routinely at negligible levels, in time frames matching increases in ERV activity have been identified in our province, as seen in Fig.…”
supporting
confidence: 54%
“…Our study indicates an increase in daily ED visits for Ͻ18-year-old Albertans for ILI, shortness of breath, and cough/congestion that was significantly higher (RR, 1.24; 95% CIs, 1.11, 1.40) in 2014 than during the same period of time in 2013. Previous studies have identified increases in asthma admissions in Canada and other countries during the period of July to October (7,8). Seasonal upswings in ERV activity, while other respiratory viral pathogens are routinely at negligible levels, in time frames matching increases in ERV activity have been identified in our province, as seen in Fig.…”
supporting
confidence: 54%
“…Factors known to aggravate asthma and increase the need for hospital treatment include epidemics of infectious diseases [3], pollen [4], cold air [5] and air pollution [6]. The rise observed in the number of hospitalization periods for asthmatics is attributable not only to a real increase in the disease but also to the efficient organization of treatment and patients' greater awareness of the services available.…”
Section: Aamentioning
confidence: 99%
“…Epidemiologic studies have detected viral infections in 85% of childhood asthma exacerbations 6) and in more than half of adult exacerbations; these upper respiratory infections are probably responsible for seasonal peaks of asthma related hospital admissions 46,57,58) . However, the mechanisms of HRV-induced asthma exacerbations are poorly understood.…”
Section: Asthma Exacerbationsmentioning
confidence: 99%
“…In individuals with asthma, HRV infections can cause exacerbations of asthma leading to hospitalization or utilization of emergency room facilities 13,45,46) . In animal models, enhanced lower airway responses to Sendai virus infection have been related to reduced IFN-γ production 47) .…”
Section: Association Between Hrv and Asthmamentioning
confidence: 99%